Web-Based Pistol Storage Security Monitoring System Optimization for Database Effectiveness - Lukman Nur Rokhim, Ahmad; Syafaat, Mokhammad; Kasiyanto, Kasiyanto; Widiatmoko, Dekki; Sridaryono, Aguk (Jurnal Bumigora Information Technology (BITe), 2024)
Background: Gun storage security is an important aspect in supporting operations, but manual monitoring often creates obstacles to the effectiveness and accuracy of gun storage data management. Objective: The purpose of this study is to optimize the gun storage security monitoring system with web-based technology to improve the effectiveness and accuracy of the database. Methods: The method used in this study is the development of a web server-based system that is integrated with real-time monitoring features, automatic notifications, cloud-based data storage to facilitate data access and tracking. Result: The results of this study are the creation of a system that is able to improve the accuracy and responsiveness of gun storage monitoring, as well as improve the efficiency of database management. Conclusion: In conclusion, the implementation of this web-based system has the potential to reduce security risks and significantly increase the effectiveness of monitoring in gun storage.